2019
DOI: 10.3390/jmse7090287
|View full text |Cite
|
Sign up to set email alerts
|

The Maturity of Automatic Identification Systems (AIS) and Its Implications for Innovation

Abstract: The member states of International Maritime Organization (IMO) have been leading in and enforcing the use of automatic identification systems (AIS) in the analysis of ship-to-ship collisions, vessel monitoring, and maritime traffic management offshore. This study will help non-federal stakeholders understand the AIS data and contribute to future research by assessing difficulties and improving access to data and applications. This study introduces the basics of AIS materials, shared channels, and currently dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The AIS provides static, dynamic and voyagerelated data according to the Safety Of Life At Sea (SOLAS) convention, refs. ( [107][108][109]). AIS data are detailed in Figure 5; thus, the mappings of the architecture of the vessel and the transmitted signals are both essential to the identification of its vulnerabilities.…”
Section: H Automatic Identification System (Ais)mentioning
confidence: 99%
“…The AIS provides static, dynamic and voyagerelated data according to the Safety Of Life At Sea (SOLAS) convention, refs. ( [107][108][109]). AIS data are detailed in Figure 5; thus, the mappings of the architecture of the vessel and the transmitted signals are both essential to the identification of its vulnerabilities.…”
Section: H Automatic Identification System (Ais)mentioning
confidence: 99%
“…In addition, Ducruet et al [37] conducted some tests on the accuracy of Lloyd data, and found that it collected most of the marine transportation information and that the extracted data were enough to represent the global marine network flow. Lee et al [38] indicated that the use of AIS data was beneficial to the public, enterprises, institutions, etc., and that the accessibility and availability of AIS data should be greatly enhanced. Therefore, the AIS data used in this paper are conducive to a more comprehensive discussion of the maritime network, and thus can provide more accurate optimization suggestions for the sustainable development of the port.…”
Section: Relevant Research On Evaluation Datamentioning
confidence: 99%
“…The AIS data represent the static data and the dynamic data of the ships. The dynamic data have information such as Maritime Mobile Communication Service Identification (MMSI) number, latitude and longitude, speed/course over ground, steering rate, and headings [36]. The static data include inherent information about a ship, such as the length, the breadth, the maximum draft, and the type.…”
Section: Datamentioning
confidence: 99%